2013
DOI: 10.3389/fpsyg.2013.00130
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Memory, Personality, and Individual Differences

Abstract: A number of studies investigating the relationship between personality and prospective memory (ProM) have appeared during the last decade. However, a review of these studies reveals little consistency in their findings and conclusions. To clarify the relationship between ProM and personality, we conducted two studies: a meta-analysis of prior research investigating the relationships between ProM and personality, and a study with 378 participants examining the relationships between ProM, personality, verbal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 50 publications
(117 reference statements)
6
27
1
Order By: Relevance
“…Cuttler and Graf (2007) found that conscientiousness predicted PM performance (for two of three PM tasks), Arana et al (2008) found that Brule-consciousness^predicted PM, and Pearman and Storandt (2005) also found a significant correlation with conscientiousness. By contrast, Salthouse, Berish, and Siedlecki (2004), Smith et al (2015), and Uttl, White, Wong Gonzalez, McDouall, and Leonard (2013) found no relationship between conscientiousness and PM. However, all of these findings are directed at PM accuracy (rather than PM thoughts), do not include self-generated naturalistic intentions, and are largely underpowered.…”
Section: Studymentioning
confidence: 67%
“…Cuttler and Graf (2007) found that conscientiousness predicted PM performance (for two of three PM tasks), Arana et al (2008) found that Brule-consciousness^predicted PM, and Pearman and Storandt (2005) also found a significant correlation with conscientiousness. By contrast, Salthouse, Berish, and Siedlecki (2004), Smith et al (2015), and Uttl, White, Wong Gonzalez, McDouall, and Leonard (2013) found no relationship between conscientiousness and PM. However, all of these findings are directed at PM accuracy (rather than PM thoughts), do not include self-generated naturalistic intentions, and are largely underpowered.…”
Section: Studymentioning
confidence: 67%
“…We hypothesised that higher Neuroticism might predict stronger recall of negative words, but noted that Neuroticism has not been consistently related to negative memory biases (Edwards & Collins, 2008;Uttl et al, 2013). In addition, negative verbal recall may be more closely related to Neuroticism for nouns than adjectives (Edwards & Collins, 2008), and negative words in VAMT included only four nouns, as well as four adjectives.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, negative verbal recall may be more closely related to Neuroticism for nouns than adjectives (Edwards & Collins, 2008), and negative words in VAMT included only four nouns, as well as four adjectives. But most importantly, negative memory biases may be associated with Neuroticism only in highly dysphoric or depressed individuals and most studies of neuroticism and affective memory investigate the recall of self-related affective material (Edwards & Collins, 2008;Uttl et al, 2013). In contrast, we measured recall of decontextualised words within a healthy sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that PM has a clear developmental trajectory (Kliegel et al 2008), and that both verbal (Uttl 2006; Uttl et al 2013) and nonverbal (Cockburn and Smith 1991; Maylor 1996) intelligence are related to it. Furthermore, there is some evidence for a female advantage in PM tasks (Palermo et al 2015).…”
Section: Part 2: Critical Analysis Of Studies Of Pm In Asdmentioning
confidence: 99%